2011
DOI: 10.1080/15332586.2011.581511
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Relationship Between Law Enforcement and School Security Measures and Violent Crime in Schools

Abstract: School crime is a vital concern, not only for students and faculty, but for administrators, policy makers, criminal justice personnel, and concerned citizens. Efforts to reduce crime and violence at schools have led many schools to adopt preventative strategies aimed at reducing actual crime and fear of crime. These measures include partnering with local police departments and implementing school resource officers, installing video cameras and closed circuit television systems, utilizing weapon-detection syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 25 publications
6
89
1
5
Order By: Relevance
“…The SSOCS, a nationally representative sample of U.S. public schools, is considered one of the richest datasets for studies of school violence. Data from the SSOCS have been used in many published studies throughout the last decade (Chen, 2008;Granberg-Rademacker et al, 2007;Jennings et al, 2011;Kupchik & Ward, 2014;Maskaly, Donner, Lanterman, & Jennings, 2011;O'Neill & McGloin, 2007;Patton, 2011;Phillips et al, 2014). School administrators from elementary, middle, and high schools complete the survey.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The SSOCS, a nationally representative sample of U.S. public schools, is considered one of the richest datasets for studies of school violence. Data from the SSOCS have been used in many published studies throughout the last decade (Chen, 2008;Granberg-Rademacker et al, 2007;Jennings et al, 2011;Kupchik & Ward, 2014;Maskaly, Donner, Lanterman, & Jennings, 2011;O'Neill & McGloin, 2007;Patton, 2011;Phillips et al, 2014). School administrators from elementary, middle, and high schools complete the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Despite some negative findings (Cook, Gottfredson, & Na, 2010;Na & Gottfredson, 2011), research on school resource officers has yielded the most promising results. Analyses of national data sets (Jennings, Khey, Maskaly, & Donner, 2011) and case studies in specific environments (Johnson, 1999) suggest that the presence of SROs is correlated with fewer acts of school violence. Studies incorporating multiple crime prevention techniques have also identified several variables as predictors of reduction in school violence including limited class changes (O'Neill & McGloin, 2007), closed campuses (O'Neill & McGloin, 2007), dress codes (Phillips, Turner, & Holt, 2014), identification cards (Phillips et al, 2014), security cameras (GranbergRademacker, Bumgarner, & Johnson, 2007), and uniform policies (Granberg-Rademacker et al, 2007).…”
Section: School Securitymentioning
confidence: 98%
See 2 more Smart Citations
“…For example, some studies have found that the use of more school security measures is associated with more exposure to drugs, fighting, and property crime (Tanner-Smith et al 2017), disorder, including personal attack and theft (Mayer and Leone 1999; Schreck and Miller 2003; Taylor 2010), and violence and weapon presence (Cuellar 2018; Nickerson and Martens 2008). Still other studies have had mixed findings, where some types of school security measures have a positive relationship with student victimization, others have a negative relationship, and others have no effect at all (Burrow and Apel 2008; Cheurprakobkit and Bartsch 2005; Crawford and Burns 2016; Jennings et al 2011; Sevigny and Zhang 2016). As such, there is no consensus on whether, how, and the extent to which school security measures relate to adolescent victimization.…”
Section: Existing Literature On School Security Measures Adolescent mentioning
confidence: 98%